PARADIGM RELEVANCE OF QURANIC EDUCATION TO PANCASILA STUDENT PROFILES FOR EARLY CHILDHOOD - Nadri Taja; Riyandi Baehaqi; Revi Rusdatul Jannah; Widya Mar’atus Sholihah Kunaepi (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
The background of this research is that education must be able to integrate divine and human values as formulated in the national education system that the essence of education has the goal of realizing the good personality of students. Based on this, the purpose of this study is to explore the paradigm of Quranic education and then interpret the profile of Pancasila students and find the relevance between Quranic education and the profile of Pancasila students. The method we use is a literature study with relevant literature and is interpreted as finding values, concepts, or ideas from the topics raised. The results of this study reveal that Quranic education is oriented towards building character guided by revelation which is closely related to monotheism and all aspects of life; the characteristics of Pancasila students which are the efforts of the Indonesian government to build the character of its citizens to comply with Pancasila values which consist of six components namely faith, fear of God Almighty, and noble character, global diversity, mutual cooperation, independence, critical and creative reasoning; As for the relevance of the six profiles of Pancasila students, they refer to the verses of the Al-Qur'an as the characteristics of the six profiles.